A macroeconomic model of an epidemic with silent transmission and endogenous self-isolation - Antonio Díez de los Ríos (Bank of Canada, 2020)
We study the interaction between epidemics and economic decisions in a model where (1) agents allocate their time to market and home production and social and home leisure, (2) these activities differ in their degree of contagiousness, (3) some infected individuals are indistinguishable from susceptible individuals, and (4) agents are not necessarily rational. For baseline parameter values for the COVID-19 pandemic, we find that agents partially selfisolate by allocating more time to home activities and that the effective reproduction number of the disease stabilises at one. Detection and isolation of infected individuals severely mitigate the recession caused by the pandemic.
Keywords: E1; H0; I1; 330; Coronavirus disease (COVID-19); Economic models